Characterization of Virgin Olive Oils Produced in Hatay - Bozdogan Konuskan, Dilsat; Didin, Mustafa (Asian Journal of Chemistry, 2010)
In this study, physical and chemical characteristics and fatty acids compositions of virgin olive oils obtained from 36 different olive oil plant in Hatay province in 2001/2002 crop years were determined. The physical properties of oils were determined as follows; density 0.916-0.922 g/cm3, refractive index 1.4680-1.4699, viscosity at 20 °C, 68-78 cpu. The chemical properties of oils were determined as follows; free fatty acids 0.7-6.3 %, peroxide value 9.21-25.89 meqO2/kg. Fatty acid compositions of the oils were found as follows; palmitic acid 10.84-15.81 %, palmitoleic acid 0.30-0.63 %, stearic acid 2.16-5.23 %, oleic acid 74.18-80.21 %, linoleic acid 4.12-7.40 % and linolenic acid 0.5-0.8 %.